2011
DOI: 10.3109/01480545.2011.586036
|View full text |Cite
|
Sign up to set email alerts
|

Male-mediated F1 effects in mice exposed to nonylphenol or to a combination of X-rays and nonylphenol

Abstract: Nonylphenol (NP) is an environmental chemical with estrogenic activity. Exposure of the general population to radiation and NP is, very often, unavoidable because of the presence of both agents in the environment of human life and work. The aim of the study was to investigate the effect of subchronic 8-week exposure to NP alone or in combination with X-rays on sperm quantity and quality and on the possibility of the transmission of mutations induced in germ cells to the next generation. Eight-week exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…It has also been shown that the number of apoptotic cells in seminiferous tubules of treated rats was increased in a dose dependent manner. Similarly, Dobrzyńska [17] reported that eight-week exposure to NP and X-ray/NP combination reduced sperm counts while it increased the percent of abnormal spermatozoa and DNA damage in gametes in mice. Karadeniz et al [45] reported that increasing concentration of NP dissolved in ethanol cause guanine oxidation in DNA determined by carbon nano-tube electrode.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…It has also been shown that the number of apoptotic cells in seminiferous tubules of treated rats was increased in a dose dependent manner. Similarly, Dobrzyńska [17] reported that eight-week exposure to NP and X-ray/NP combination reduced sperm counts while it increased the percent of abnormal spermatozoa and DNA damage in gametes in mice. Karadeniz et al [45] reported that increasing concentration of NP dissolved in ethanol cause guanine oxidation in DNA determined by carbon nano-tube electrode.…”
Section: Discussionmentioning
confidence: 94%
“…In vivo estrogenic activity of NP is much more potent than that of in vitro estrogenic activity of NP [37] . Exposure of the general population to NP is unavoidable because of the presence of the agent in the environment [17] . The effects of NP on livestocks have been described such as disruption in testicular development, decrease in sperm motility, viability, decrease in sperm count which eventually led to the decrease in male fertility [12][13][14]38] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, DBP is known to affect both the number and diversity of soil microorganisms (Cartwright et al, 2000;Kapanen et al, 2007;Jun et al, 2009). Both NP and DBP are known to be toxic to mammals (Cirillo et al, 2011;Dobrzyńska, 2012), and there is some evidence that they can also be deleterious to soil nematodes, earthworms, enchytraeids, and collembolans (Domene et al, 2009;Hood et al, 2000). However, little effort has been made as yet to document their effect on soil microflora and, as a result, little is known regarding the mechanisms involved in the interaction between these EDCs and the soil biota.…”
Section: Introductionmentioning
confidence: 95%